Domain-specific evaluation of Croatian speech synthesis in CALL - Dunđer, Ivan; Arambašić, Marko; Seljan, Sanja (2013)
Formant speech synthesis method mimics the time-varying formant frequencies of human speech and does not use prerecorded speech samples. In this paper, related work is discussed and an experiment is conducted using formant synthesis-based text-to-speech tool CroSS (Croatian Speech Synthesizer), in order to assess and evaluate the quality of synthesized Croatian speech, according to five criteria, then by domain suitability, affective attitudes and appropriateness of implementation in broader public use and in Computer-assisted Language Learning (CALL). The aim of integrating speech synthesis technology in Computer-assisted Language Learning resulted from the need to provide an interactive learning and teaching environment. This paper also addressed weaknesses and problems of Croatian language (e.g. input preprocessing of word classes) in the process of text-to-speech synthesis. The results are discussed and suggestions for further research mentioned.
Projekt MZOS
ENG